Smithiomyces dominicanus (Agaricales: Agaricaceae), a new species from the Dominican Republic - Justo, Alfredo; Angelini, Claudio; Bizzi, Alberto (Phytotaxa, 2015)
Smithiomyces dominicanus is described as new, based on collections made in the Dominican Republic. Morphologically this taxon is very similar to S. mexicanus, but differs in the non-umbonate pileus, the broad stipe base and the smooth basidiospores as seen under light microscope, but with isolated, small warts under SEM. Molecular (nrITS) data also supports the recognition of this taxon as a separate species.